High-performance sport management in Latvia: a review of sport federations' managers view - Dombrovska, A.; Luika, S. (LASE Journal of Sport Science, 2018)
The current economic environment throws a sharper focus on sport management and the performance of sport organizations than ever before. All governments play an active and a crucial role in developing and supporting the sporting life of their nations. This is true at the high-performance level and in community sport systems for people of all ages and abilities. Growing body of literature highlights the importance of sport organizations in high-performance sport management and success. Robinson, Chelladurai, Bodet, and Downward (2012) point out that there is no model of governance that will transform a poor-performing organisation into a pillar of high-performance. The performance of the board is almost entirely dependent on the people involved; models or frameworks can only help them by providing tools to work with. The purpose of this paper is to examine the process of Latvian high-performance sport management from an organisational perspective of 89 national sport organisations - recognised sport federations. The study is based on a review of laws and regulations and a survey. Managers of sport federations were contacted to complete an online survey, a questionnaire related to theoretical issues. Overall, 50 federations completed the questionnaire. The data were analysed with the method of descriptive statistics. The results show that it is necessary to pay more attention to specific factors - the high-performance sport development planning in the long-term, involving more participants in the sport; development of talent recognition, sport development system in the country, and athlete support during and after career. In order to provide high quality training opportunities, it is necessary to ensure education forcoaches and develop sport infrastructure. Also, it is essential to ensure scientific support for sport.